Transforaminal Endoscopic Thoracic Discectomy Is More Cost-Effective Than Microdiscectomy for Symptomatic Disc Herniations - Junseok Bae; Pratyush Shahi; Sang-Ho Lee; Han-Joong Keum; Ju-Wan Seok; Yong-Soo Choi; Jin-Sung Kim (Neurospine)
Objective To analyze costs and cost-effectiveness of transforaminal endoscopic thoracic discectomy (TETD) for the treatment of symptomatic thoracic disc herniation (TDH) and compare it with open microdiscectomy (MD). Methods This retrospective cohort study included patients who underwent TETD or MD for symptomatic TDH and had a minimum follow-up of 1 year. Cost analysis included direct costs (primary and secondary hospital costs), indirect costs (lost wages due to work absence), total costs (direct + indirect), and cost-effectiveness (cost per quality-adjusted life year [QALY] and incremental cost-effectiveness ratio [ICER]). Clinical outcomes included patient-reported outcome measures (Oswestry Disability Index [ODI], 36-item Short Form health survey [SF-36]), QALY gained, and reoperation and readmission rates at 1 year. TETD and MD groups were compared for outcome measures. Results A total of 111 patients (57 TETD, 54 MD) were included. The direct ($6,270 TETD vs. $7,410 MD, p < 0.01), indirect costs ($1,250 TETD vs. $1,450 MD, p < 0.01), total costs ($7,520 TETD vs. $8,860 MD, p < 0.01), and cost per QALY ($31,333 TETD vs. $44,300 MD, p < 0.01) were significantly lower for TETD compared to MD. ICER of TETD was found to be -$33,500. At 1 year, TETD group showed significantly greater improvement in ODI (46% vs. 36%, p < 0.01) and SF-36 (64% vs. 53%, p < 0.01) and significantly greater QALY gained (0.24 vs. 0.2, p < 0.01) compared to MD group. No significant difference was found in reoperation and readmission rates. Conclusion TETD demonstrated significantly better clinical outcomes, lower overall costs, and better cost-effectiveness than MD in appropriately selected patients of symptomatic TDH.